Estimates of the macroeconomic costs of cyber‐attacks. Issue 2 (18th June 2020) - Dieye, Rokhaya; Bounfour, Ahmed; Ozaygen, Altay; Kammoun, Niaz
Abstract: This paper estimates the macroeconomic losses related to the cyber‐attacks originating from the information and communications technology (ICT) and the financial sectors. The study accounts for the interdependency of various economic sectors and looks to the cascading effect of cyber‐attacks on production network in the United States and leading Organisation for Economic Co‐operation and Development countries with the help of the input–output methodology and the World Input–Output Database. Our results suggest that cyber‐attacks that affect the ICT and finance sectors result in losses which also impact different economic sectors, due to cascading effects.